Soil classification analysis based on piezocone penetration test data - A case study from a quick-clay landslide site in southwestern Sweden - Abbaszadeh Shahri, A.; Malehmir, A.; Juhlin, Christopher (Elsevier, 2015)
© 2015 Elsevier B.V. Cone penetration test (CPT) and piezocone penetration test (CPTu) methods can be effective in site characterization and are important for soil profiling and classification. Extensive experience exists that relates CPT and CPTu results to soil type/state and these are often the preferred in-situ tools for subsurface investigations, soil exploration and the evaluation of different engineering soil properties, compared with conventional laboratory testing. In this study, eight methods, consisting of traditional and nontraditional ones, for soil classification and prediction of soil type and state using CPTu data were examined and tested. The CPTu data not only provide valuable information on soil types, but also can be used for deriving correlations with engineering soil properties for the purposes of hazard analyses and design of foundations. We carried out and established a region-specific correlation between CPTu data and soil properties for three location test points in southwestern Sweden at a quick-clay landslide site. First, an analysis of the available CPTu data was performed and then classification of the soils was made. After determination and identification of the soil profiles, the results were further evaluated using the Unified Soil Classification System (USCS) and converted to CPT-SPT charts. We summarize results from each of these methods, including a description of the available charts and their performance for soil classification. From CPTu data, we provide high-resolution soil profiles from the three test points. Our work allowed the detection of potential sensitive fine-grained clays, which are responsible for landslides in the study area, however, in most cases occurring above coarse-grained materials. These materials were also detected in the CPTu data and show good correspondence with available reflection seismic profiles from the site.